Risk Governance: Examining its Impact Upon Bank Performance and Risk - Gontarek, Walter (Cranfield University, 2017)
This study examines the emergence of risk governance arrangements in US bank holding companies (BHCs) and tests for their impact upon performance and risk profiles. Following the financial crisis, regulators introduced several new risk governance processes, including the adoption of Risk Appetite arrangements and the establishment of Risk Committees, both board level features. In this study, a research gap is unearthed with respect to risk governance practices and their impact upon BHC performance and risk measures. The motivation of this research is to validate the adoption of these board-level practices in an evidence-based framework. The empirical research method relies on the collection of a unique data set. The sample covers a significant dollar-weighted portion of the US banking system. Multivariate analysis facilitates the testing of risk governance mechanisms to outcome variables, while controlling for firm-specific and standard corporate governance variables. The practical implication of this study with respect to Risk Appetite is clear. BHCs that practice Risk Appetite arrangements exhibit improved performance and lower realised loan losses. In contrast, while some limited evidence is presented that the marketplace may reward BHCs for certain composition aspects of the Risk Committee, the overall results suggest that the requirement for a Risk Committee has little impact to BHC’s operating performance and risk measures. In terms of academic contribution, this study examines two major risk governance mechanisms within a common framework, presenting evidence of a significant and positive impact of the board level articulation of Risk Appetite arrangements to a suite of BHC performance measures and a negative association to loan losses. As the first known empirical research study of Risk Appetite, it confirms that this board level mechanism should be included as an explanatory variable in bank or risk governance related empirical research studies. These findings provide industry practitioners (including BHC chief executive officers and board members) convincing arguments for the immediate adoption of Risk Appetite arrangements. US Regulators, who introduced Risk Appetite requirements in 2014 for larger BHCs, are presented with validation by this study for wider adoption of this risk governance mechanism, even if such practices are voluntarily adopted by BHCs. As signs begin to emerge in the United States of the possible relaxation of the regulatory requirements of certain aspects of the Dodd-Frank Act, this study contributes to this debate in a timely fashion by testing the veracity of two key supervisory-driven risk governance practices aimed at the boardroom in an evidence-based evaluation.
Keywords: Risk Governance; Corporate Governance; BHCs; Risk Appetite; Risk Committee